The Relationship of the Macroeconomic Variables with the Growth of Garment Industry in Bangladesh - Hossain, Sk. Alamgir; Islam, K. M. Anwarul (Global Disclosure of Economics and Business, 2015)
In this research paper, we have tried to find out the relationship between the growth rate of garment industry and the macroeconomic variables. And for this we have conducted three types of analysis. First one is quantitative analysis; a second one is qualitative analysis, and the last one is a beta concept. Quantitative analysis has covered graphical presentation and multiple regression analysis. The graphical presentation just provides an overall idea about the relationship of variables, but it is an abstract concept. In case of regression analysis, we have used one dependent variable that is the growth rate of garment industry and seven independent variables those are growth rate of real GDP, the unemployment rate, inflation rate, interest rate, level of stock market, exchange rate. And stata-10 software has been used to run the regression model. After running the programmed it is seen that there have some econometric problems. By using the logarithm, we have solved those problems. A multiple regression analysis has been made to know the extent to which these variables affect the garment export growth rate. From that analysis, it has been found that about 70% variations in the growth rate of garments export can be defined by these variables. Then an equation for predicting future garments export has been constructed. Qualitative analysis has encompassed economic and political issues. After this, for knowing the individual effect of the variables, a beta concept has been employed and from that analysis it has been found that no variable affect garments export to a large extent. At the end of the analysis it can be said that, individual effect of the macroeconomic variables on the growth rate of garments export is not much but when they are combined, they can influence the garments export growth rate. As they are also related with each other which means change in one macroeconomic variable may change all the other variables. Therefore, a combined effect always remains. So, we can say that macroeconomic variables influence the garment industry of our country but not to a great extent.JEL Classification Code: E60, M10, L67, O14